Leader of the pack : tales of an urban werewolf - MacInerney, Karen, 1970- (A Ballantine Books Mass Market Original, 2009)
"On the outside, Sophie Garou is living every woman's dream: She has beauty, brains, and a big-time position in Austin's most respected accounting firm (not to mention a very sexy, very successful new boyfriend). But there's one thing Sophie would rather keep under wraps: She's a werewolf. Sophie's life gets a little more hairy when her long-estranged father, Luc, arrives in the Live Music Capital to attend the werewolves' annual Howl and reconnect with his daughter. But Luc's plans fall apart after he's accused of murder and arrested by his archrival, Wolfgang, leader of the Houston pack (and one notoriously dirty dog). Wolfgang drools at the thought of Luc's impending execution, but Sophie won't let her father die without a fight. Determined to prove his innocence, she and her friends set out to find the real killer. Along the way, Sophie must deal with taboo attractions, Machiavellian intrigues, sinister agendas, and hair-raising betrayals."--p. [4] of cover.